Assessment of esophageal body peristaltic work using functional lumen imaging probe panometry - Acharya, Shashank (Am J Physiol Gastrointest Liver Physiol, 2021)
The goal of this study was to conceptualize and compute measures of “mechanical work” done by the esophagus using data generated during functional lumen imaging probe (FLIP) panometry and compare work done during secondary peristalsis among patients and controls. Eighty-five individuals were evaluated with a 16-cm FLIP during sedated endoscopy, including asymptomatic controls (n = 14) and those with achalasia subtypes I, II, and III (n = 15, each); gastroesophageal reflux disease (GERD; n = 13); eosinophilic esophagitis (EoE; n = 9); and systemic sclerosis (SSc; n = 5). The FLIP catheter was positioned to have its distal segment straddling the esophagogastric junction (EGJ) during stepwise distension. Two metrics of work were assessed: “active work” (during bag volumes ≤ 40 mL where contractility generates substantial changes in lumen area) and “work capacity” (for bag volumes ≥ 60 mL when contractility cannot substantially alter the lumen area). Controls showed median [interquartile range (IQR)] of 7.3 (3.6–9.2) mJ of active work and 268.6 (225.2–332.3) mJ of work capacity. Patients with all achalasia subtypes, GERD, and SSc showed lower active work done than controls (P ≤ 0.003). Patients with achalasia subtypes I and II, GERD, and SSc had lower work capacity compared with controls (P < 0.001, 0.004, 0.04, and 0.001, respectively). Work capacity was similar between controls and patients with achalasia type III and EoE. Mechanical work of the esophagus differs between healthy controls and patient groups with achalasia, EoE, SSc, and GERD. Further studies are needed to fully explore the utility of this approach, but these work metrics would be valuable for device design (artificial esophagus), to measure the efficacy of peristalsis, to gauge the physiological state of the esophagus, and to comment on its pumping effectiveness. NEW & NOTEWORTHY Functional lumen imaging probe (FLIP) panometry assesses esophageal response to distension and provides a simultaneous assessment of pressure and dimension during contractility. This enables an objective assessment of “mechanical work” done by the esophagus. Eighty-five individuals were evaluated, and two work metrics were computed for each subject. Controls showed greater values of work compared with individuals with achalasia, gastroesophageal reflux disease (GERD), and systemic sclerosis (SSc). These values can quantify the mechanical behavior of the distal esophagus and assist in the estimation of muscular integrity.